2008
DOI: 10.1111/j.1745-459x.2008.00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Location and Scale Influence on Sensory Acceptability Measurements Among Low‐income Consumers

Abstract: The adequate methodology to measure food acceptability among low‐income population was researched. Two locations (home and central locations) and two scales (number and box scales) were tested. One hundred and twelve subjects from low‐income households measured four samples (two chocolate milks and two soups). Samples had higher scores in the home location than in the central location. In the central location consumers were more critical than in the home location test. If sensory acceptability discrimination i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 14 publications
3
30
0
1
Order By: Relevance
“…This indicated that the CLT setting has a higher discriminating power as previously observed by Boutrolle et al. (2005) and Sosa et al. (2008).…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…This indicated that the CLT setting has a higher discriminating power as previously observed by Boutrolle et al. (2005) and Sosa et al. (2008).…”
Section: Resultssupporting
confidence: 69%
“…Boutrolle et al. (2005) and Sosa et al. (2008) showed that consumers in a CLT discriminated somewhat more between products than in a HUT situation.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Sealed cans sat in simmering water for 45 min, heating the soup to 71C. Barylko‐Pikielna and Kostyra (2007) and Sosa et al. (2008) heated soup samples to 70C in a study to understand the sensory interaction of umami substances in model food systems.…”
Section: Methodsmentioning
confidence: 99%
“…Home usage tests (HUT) and central location tests (CLT) have been compared in measuring the acceptability of food products (Boutrolle and others 2007; Sosa and others 2007) yet there are no published results comparing optimum concentration levels of food ingredients obtained in HUT and CLT.…”
Section: Introductionmentioning
confidence: 99%